Certain Applications via \((α, β)\)-\(Z\)-Contraction Type Fixed Points in Bipolar Parametric Metric Space - Rani, K. Jyothirmayi; Najaraju, V. (Communications in Mathematics and Applications, 2025)
This work defines \((α, β)\)-\(Z\) contraction mappings to establish fixed point results in a bipolar parametric metric space. Our findings generalize and enhance several well-known results from the fixed point (FP) theory literature. A good example is also provided to confirm the veracity of the acquired results. In addition, we provide applications for homotopy and integral equations, as well as an explanation of the significance of the obtained results.